2008
DOI: 10.1007/s00520-008-0493-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of men treated for localized prostate cancer: outcomes at 6 and 12 months

Abstract: Physiological symptoms and psychological symptoms were both significant predictors of QOL. The psychological factors that predicted quality of life in this study have potential for intervention and point to the next stage of the research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 18 publications
3
24
1
4
Order By: Relevance
“…All symptoms peaked after one month with irritation symptoms and annoyance being the worst (Anderson et al, 2009). Other studies showed a peak in severity at three months after treatment, with nocturia being the most severe symptom (Lev et al, 2009;Tsui et al, 2005). A significant amount of discomfort remained for several weeks and up to 6 months after the end of treatment for patients who were treated with brachytherapy (Faithfull, 1995).…”
Section: Symptomsmentioning
confidence: 94%
“…All symptoms peaked after one month with irritation symptoms and annoyance being the worst (Anderson et al, 2009). Other studies showed a peak in severity at three months after treatment, with nocturia being the most severe symptom (Lev et al, 2009;Tsui et al, 2005). A significant amount of discomfort remained for several weeks and up to 6 months after the end of treatment for patients who were treated with brachytherapy (Faithfull, 1995).…”
Section: Symptomsmentioning
confidence: 94%
“…The perception of stress as a threat elicits negative emotional states and maladaptive coping, whereas the perception of stress as a challenge is associated with favourable emotional reactions and greater confidence in coping17. A number of studies have reported significant associations between perceived stress and overall quality of life in mixed cancer groups18 and in men with localised prostate cancer1920. In the emotional domain, Hsaoi et al21 found a significant association between global perceived stress and greater prostate cancer symptom distress one to three months post treatment and stress appraisal predicted total mood disturbance in a group of men two years post treatment22.…”
mentioning
confidence: 99%
“…Studies have shown that the level of self-efficacy influences breast cancer patient's quality of life and self-care behavior, but it decreases or stabilizes over time (13)(14)(15). On the other hand, age is associated with the patient's self-efficacy that may increase as a person grows older (16,17).…”
Section: Objectivesmentioning
confidence: 99%